2019
DOI: 10.3389/fpls.2019.00197
|View full text |Cite
|
Sign up to set email alerts
|

OsNAR2.1 Positively Regulates Drought Tolerance and Grain Yield Under Drought Stress Conditions in Rice

Abstract: Drought is an important environmental factor that severely restricts crop production. The high-affinity nitrate transporter partner protein OsNAR2.1 plays an essential role in nitrate absorption and translocation in rice. Our results suggest that OsNAR2.1 expression is markedly induced by water deficit. After drought stress conditions and irrigation, compared with wild-type (WT), the survival rate was significantly improved in OsNAR2.1 over-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 61 publications
(103 reference statements)
1
35
0
Order By: Relevance
“…The OsNRT2.1-overexpressing rice plant not only enhanced vegetative growth under low N conditions [42], but also enhanced the yield compared to the wild type under alternating wet and dry conditions [44] and drought stress [45] by increasing nitrogen uptake. This gene also promoted root elongation via auxin transport [43].…”
Section: Discussionmentioning
confidence: 98%
“…The OsNRT2.1-overexpressing rice plant not only enhanced vegetative growth under low N conditions [42], but also enhanced the yield compared to the wild type under alternating wet and dry conditions [44] and drought stress [45] by increasing nitrogen uptake. This gene also promoted root elongation via auxin transport [43].…”
Section: Discussionmentioning
confidence: 98%
“…Overexpression of OsNAR2.1 had a positive impact on vegetative growth following treatment with PEG, and the transgenic lines had greater grain yield after drought treatment in a pot trial. Expression of genes associated with osmotic regulation in plants was altered by the overexpression of OsNAR2.1 , suggesting that there are molecular links between the two regulatory systems ( Chen et al , 2019 ). Increased NH 4 + supply improved the rate of water uptake and root hydraulic conductance, and increased transcript levels of several aquaporin genes in rice ( Ishikawa-Sakurai et al , 2014 ; Ren et al , 2015 ).…”
Section: The Intricate Interaction Between Nitrogen Uptake and Water mentioning
confidence: 99%
“…We also demonstrated that the expressions of genes related to N-uptake and N-transport were increased by C. bipunctata feeding, even in N-deficiency conditions. It has been reported that the expressions of OsNRT2.1 and OsNRT2.3a respond not only to nitrate concentration but also to drought stress [ 25 ]. Yang et al reported that rice infected by the endophytic fungus Phomopsis liquidambari showed substantial changes in N uptake and N metabolism [ 26 ].…”
Section: Discussionmentioning
confidence: 99%